2003
DOI: 10.1097/01.lab.0000048721.21475.d1
|View full text |Cite
|
Sign up to set email alerts
|

Apoptosis and Apoptosis-Related Molecules in the Submandibular Gland of the Nonobese Diabetic Mouse Model for Sjögren's Syndrome: Limited Role for Apoptosis in the Development of Sialoadenitis

Abstract: SUMMARY:Sjögren's syndrome is an autoimmune disease in which lymphocytic infiltrates develop in the exocrine glands.Pathogenetic aspects of the disease can be studied in the nonobese diabetic (NOD) mouse strain, a spontaneous model for Sjögren's syndrome. Apoptosis may play a role in the initation phase and in the effector phase of autoimmune diseases. Here, we have examined the role of apoptosis in the development of sialoadenitis in the NOD mouse. Apoptotic cells and the expression of apoptosis-related molec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
1

Year Published

2003
2003
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 36 publications
1
7
1
Order By: Relevance
“…2). A role of apoptosis of epithelial cells in the effector phase of sialoadenitis in the NOD mouse was suggested after the study of some investigators (52)(53)(54)(55)(56)(57), while other investigators did not find evidence for a role of apoptosis in the effector phase of sialoadenitis (58). In addition, in our experiments we did not find evidence for a role of apoptosis in the initiation phase of IDDM and SS in either group of mice.…”
Section: Discussioncontrasting
confidence: 47%
“…2). A role of apoptosis of epithelial cells in the effector phase of sialoadenitis in the NOD mouse was suggested after the study of some investigators (52)(53)(54)(55)(56)(57), while other investigators did not find evidence for a role of apoptosis in the effector phase of sialoadenitis (58). In addition, in our experiments we did not find evidence for a role of apoptosis in the initiation phase of IDDM and SS in either group of mice.…”
Section: Discussioncontrasting
confidence: 47%
“…Activated CD4 + T cells can trigger CD8 + T cell differentiation which could lead to lacrimal epithelial cell death through Fas-FasL system or by releasing perforin-granzyme. Expression of FasL and its receptor Fas, have been observed in the lacrimal (Tsubota et al, 2003) and salivary glands of SS patients (Matsumura et al, 1996) and in the salivary glands of the NOD mice (Van Blokland et al, 2003). The interaction of Fas and FasL initiates a chain of biochemical events which leads to cleavage and activation of caspase 3 with subsequent substrate cleavage and apoptosis (Manganelli and Fietta, 2003; Kulkarni et al, 2006; O’Brien and Kirby, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…Some studies suggested that apoptosis of the lacrimal and salivary gland epithelial cells in SS is responsible for the decreased secretory function of these glands (Humphreys-Beher et al, 1999, Tsubota et al, 2003. However, other studies showed limited roles for apoptosis in SS (Ohlsson et al, 2001, Van Blokland et al, 2003. The different experimental approaches used in these studies might explain some of the discrepancies.…”
Section: Mechanisms Of Lacrimal Gland Dysfunctionmentioning
confidence: 99%